Discovery of a new species of the brachyelytrous net-winged beetle genus Alyculus (Coleoptera: Lycidae) from Peninsular Malaysia - Takahashi, Naoki; Bocák, Ladislav; Ghani, Idris Abd (Zootaxa, 2016)
The net-winged beetle genus Alyculus Kasantsev is reported from Peninsular Malaysia for the first time and a new species, A. malaypeninsularis sp. nov., is described and illustrated. An expanded identification key to Alyculus males is provided and the biology and distribution of the species are discussed.
Keywords: Coleoptera; brouci; Malaysia; druhová specificita; Animal Distribution; Male; Animals; mužské pohlaví; rozšíření zvířat; zvířata; Species Specificity; Malajsie